Patient’s values and preferences for stroke prevention in atrial fibrillation: balancing stroke and bleeding risk with oral anticoagulation - Lane, Deirdre A.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2014)
Note: The review process for this editorial was handled by Christian Weber, Editor in Chief.